Характеристика роботи насоса з відцентрово-вихровим ступенем порівняно з насосом типу ЕВН - Антоненко, Сергій Сергійович; Колісніченко, Едуард Васильович; Кондусь, Владислав Юрійович; Ратушний, Олександр Валерійович; Ковязін, Олексій Сергійович; Antonenko, Serhii; Kolisnichenko, Eduard; Kondus, Vladyslav; Ratushnyi, Оleksandr; Koviazin, Oleksii (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Розвиток галузі насособудування супроводжується пошуком шляхів удосконалення технологій, методів проєктування й виготовлення насосного обладнання з метою підвищення його ефективності. Сучасні вимоги до насосних систем диктують необхідність створення агрегатів, здатних стабільно працювати в широкому діапазоні подач і напорів, адаптуючись до змінних умов експлуатації та властивостей перекачуваного середовища Особливу складність становить транспортування високов’язких рідин, що потребує нових конструктивних рішень. У роботі проведено експериментальні дослідження гідравлічних характеристик насоса з відцентрово вихровим ступенем при різних частотах обертання робочого органу. На основі отриманих даних побудовано робочі характеристики, здійснено порівняльний аналіз енергоефективності й проведено зіставлення з електровідцентровими насосами (далі – ЕВН). Визначено оптимальні режими функціонування й окреслено перспективні ділянки застосування насосів із відцентрово-вихровими (далі – ВВ) ступенями для роботи з високов’язкими середовищами. /// EN: The development of the pump industry was accompanied by a search for ways to improve technologies, design methods and equipment manufacturing. The purpose of these processes is to increase the efficiency of the units, reduce energy consumption and ensure stable operation under variable loads. Modern requirements dictate the creation of universal installations capable of operating in a wide range of flows and pressures, adapting to the characteristics of the pumped medium. This is important for industrial enterprises, where the reliability of the equipment determines the efficiency of technological processes. The problem of transporting highly viscous liquids, which create additional hydraulic resistance and reduce productivity, remains relevant. Its solution requires special design solutions. Progress in mechanical engineering and the development of related technologies contribute to the emergence of new approaches to pump design, which ensure the efficiency of work with highly viscous and heterogeneous media. It is important to take into account changes in the composition and physicochemical characteristics of liquids, as they significantly affect the parameters of the systems and form new requirements for pumps, in particular regarding materials and operating modes. The paper presents the results of an experimental study of the hydraulic characteristics of a pump with a centrifugal-vortex stage at different speeds of rotation of the working body. The operating characteristics were constructed, a comparative analysis of energy efficiency depending on the speed was carried out and a comparison was made with electric centrifugal pumps. The optimal operating modes were determined, ensuring maximum productivity at minimal energy costs, and promising areas of application of pumps with centrifugal-vortex stages in industrial processes related to pumping complex media were outlined.
Performance characteristics of a pump with a centrifugal-vortex stage in comparison with an electric centrifugal PUMP
Keywords: насос; робоче колесо; ступінь; подача; напір; потужність; ККД; енергоефективність; pump; impeller; stage; flow; pressure; power; efficiency; energy efficiency